Factors Associated With Positive Self-Rated Health: Comparing Older Adults in Brazil and in Portugal - Cachioni, Meire; Cipolli, Gabriela Cabett; Borim, Flávia Silva Arbex; Batistoni, Samila Sathler Tavares; Yassuda, Mônica Sanches; Neri, Anita Liberalesso; Paúl, Constança (Frontiers in Public Health, 2021)
Introduction: Self-rated health is a multidimensional health indicator and a predictor of adverse events in old age. Answers to this assessment are influenced by social, cultural and personality factors. Aim: Exploring common and distinctive characteristics of Brazilian and Portuguese older adults aged 70 and over regarding positive self-rated health according to sociodemographic variables, to functional capacity, to independent performance of basic activities of daily living and to neuroticism, as well as analyzing associations between positive self-rated health and these variables. Methods: The present paper is a comparative and cross-sectional study based on secondary data contained in the databases of the FIBRA (Frailty in Brazilian Older Adults) follow-up study, with 418 Brazilian older adults, and of the DIA (From Disability to Activity: The Challenge of Aging) study, with 380 Portuguese older adults. Both samples had higher percentages of women: 68.4% for Portugal and 69.9% for Brazil. The Brazilian sample had a higher average age (80.31 ± 4.67) than the Portuguese sample (76.80 ± 5.28). Results: The Portuguese older adults had better overall cognition scores, higher handgrip strength and higher neuroticism values than the Brazilian older adults. In the simple and multiple logistic regression analyses, it was found that among Brazilian older adults, subjects with higher scores in the MMSE (OR 1.16; 95% CI 1.08–1.24), regardless of ADL performance (OR 2.13; 95% CI 1.31–3.47) and with scores 24–29 (OR 1.92; 95% CI 1.07–3.43) or 11–23 (OR 2.09; 95% CI 1.15–3.79) in neuroticism were more likely to assess their health as very good/good. On the other hand, the Portuguese older adults with intermediate 24–9 (OR 2.38; 95% CI 1.31–4.33) or low 11–23 (OR 5.31; 95% CI 2.69–10.45) scores in neuroticism were more likely to evaluate their health as very good/good. Conclusion: Based on the findings of the present study and on the existing literature, it may be said that it is possible for people to age while keeping a positive perception of their own health, even in advanced old age; comparisons between the above-mentioned countries, however, point to the need for investments in healthcare systems so that older adults may enjoy greater physical independence and improved mental health.